2019
DOI: 10.3168/jds.2019-16822
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions of stored manure from dairy cows fed conventional or brown midrib corn silage

Abstract: The objective of this study was to examine the effects of feeding conventional corn silage (CCS) or brown midrib corn silage (BMCS) to dairy cows on CH 4 emissions from stored manure. Eight lactating cows were fed (ad libitum) a total mixed ration (forage: concentrate ratio 65:35; dry matter basis) containing 59% (dry matter basis) of either CCS or BMCS. Feces and urine were collected from each cow and mixed with residual sludge obtained from a manure storage structure. Manure was incubated for 17 wk at 20°C u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Maximal CH 4 emission potential averaged 148 L/kg of VS and was not affected by frequency of diet delivery, which was consistent with the absence of treatment effect on VS and NDF excreted (Table 10). In this study, the observed values of maximal CH 4 production potential of manure are within the range of values (85 to 197 L/kg of VS) observed in our previous studies (Massé et al, 2016;Benchaar and Hassanat, 2019; Benchaar and Hassanat: FREQUENCY OF DIET DELIVERY TO DAIRY COWS Means within rows with different lowercase superscripts differ (P < 0.05).…”
Section: Chemical Composition Of the Mixture Of Feces And Urine And Manure Methane Emissionssupporting
confidence: 86%
See 1 more Smart Citation
“…Maximal CH 4 emission potential averaged 148 L/kg of VS and was not affected by frequency of diet delivery, which was consistent with the absence of treatment effect on VS and NDF excreted (Table 10). In this study, the observed values of maximal CH 4 production potential of manure are within the range of values (85 to 197 L/kg of VS) observed in our previous studies (Massé et al, 2016;Benchaar and Hassanat, 2019; Benchaar and Hassanat: FREQUENCY OF DIET DELIVERY TO DAIRY COWS Means within rows with different lowercase superscripts differ (P < 0.05).…”
Section: Chemical Composition Of the Mixture Of Feces And Urine And Manure Methane Emissionssupporting
confidence: 86%
“…Diet manipulation has been shown to influence CH 4 production in dairy cows (Brask et al, 2013;Benchaar et al, 2015;Hassanat et al, 2017). When dietary interventions affected DMI or ruminal OM fermentation, the amount and the composition of manure volatile solids (VS) were changed, affecting CH 4 emissions from stored manure (Møller et al, 2014;Benchaar and Hassanat, 2019;Hassanat and Benchaar, 2019). However, studies investigating the effect of non-nutritional feeding management practices (e.g., frequency of diet delivery) on CH 4 emissions from enteric fermentation and manure storage are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Partial replacement of GS by CS resulted in a numerical increase in OM output in the feces. Similarly, Benchaar and Hassanat [ 23 ] found that dairy cows fed midrib corn silage excreted more volatile solids than cows fed conventional corn silage. The OM output in the present study was also numerically higher for the diets supplemented with RSO.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of CH 4 emitted from manure is small compared with the total amount of enteric CH 4 produced by ruminants 20 . However, emission from manure in feedlots is relevant, because large volumes of manure can result in higher CH 4 emission 21 .…”
Section: Introductionmentioning
confidence: 95%